HERMENEUTIKA SEBAGAI METODE BARU DALAM MENAFSIRKAN ALQURAN - Mulizar, Mulizar (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2017)
This article will discuss hermeneutics as a new method of interpreting the Quran.The use of hermeneutics is a new thingin the world of interpretation. Some support and some reject it.The results of this study show that the use of hermeneutics in interpreting the Qurâan must be careful.In addition, This science should be placed as a complement, not as a subdivision of the science of interpretation. On the other hand, hermeneutics paves the way to contextualize the scriptures, so that they can dialogue in different spaces and times, as apologically desirable and held by many religious groups to their respective scriptures.